Spinal cord compression secondary to intraspinal extramedullary hematopoiesis - Foziah J AlShamrani; Noor M AlMohish; Fahad A AlDawsari; Jaafer J AlObaid; Ibrahim A AlGhanimi; Abdullah A AlNahdi (Wolters Kluwer Medknow Publications, 2023)
Extramedullary hematopoiesis (EMH) is a rare cause of spinal cord compression (SCC) occurring in various hematological illnesses such as myeloproliferative disorders, thalassemias, and various types of anemia. EMH represents the growth of blood cells outside the bone marrow. Common EMH locations include the spleen, liver, lymph nodes, and paravertebral regions. When this occurs in the spinal cord, the mass effect can compress the spinal cord and cause different neurological symptoms depending on the area of the spinal cord affected. This report describes a 27-year-old female with a known case of beta-thalassemia major, who presented with mid-thoracic back pain, weakness, and paresthesia at the T10 level. In addition, this report illustrates the importance of considering EMH in the differential diagnosis of SCC in patients with thalassemia.